A grouting material based on dopamine in-situ polymerization modification and its preparation method and application

By using grouting materials based on dopamine in situ polymerization modification in loose crushed tunnels of coal mines, the slurry leakage problem is solved, the reinforcement effect is improved, and the cost is reduced.

CN118993674BActive Publication Date: 2025-03-07CCTEG COAL MINING RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410939000.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-03-07
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

In loose and broken tunnels of coal mines, the existing grouting materials have serious slurry leakage, resulting in poor reinforcement effect.

Method used

Using a grouting material based on dopamine in situ polymerization modification, the in situ polymerization reaction is achieved by adding dopamine active monomer to component A and combining it with components such as polymerization catalyst, polymerization catalyst and other components in component B, and quickly solidify to avoid slurry leakage.

Benefits of technology

It effectively solves the serious problem of slurry leakage in loose and broken coal mine tunnels, improves the strength and toughness of grouting materials, improves the reinforcement effect, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993674B_ABST
    Figure CN118993674B_ABST
Patent Text Reader

Abstract

The invention discloses a grouting material based on dopamine in-situ polymerization modification and its preparation method and application, the grouting material includes component A and component B, the mass ratio of component A to component B is (0.8-1.2): (0.8-1.2); wherein component A includes the following components by mass fraction: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15-20 parts of dopamine active monomer, 1-2 parts of fluid loss reducer, 1-3 parts of reinforcing agent; component B includes the following components by mass fraction: 100 parts of gypsum, 2-5 parts of polymerization catalyst, 1 part of polymerization catalyst promoter, 1-2 parts of toughening agent, and 1-3 parts of accelerator. The present invention optimizes the formula composition of the grouting material so that the obtained grouting material has a good grouting effect, and can solve the problem of serious leakage of loose and broken coal mine tunnels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of grouting materials, and in particular, relates to a grouting material based on in-situ polymerization modification of dopamine, and a preparation method and application thereof. Background Art

[0002] As part of the complete set of control technology for surrounding rock of coal mine tunnels of "support-modification-pressure relief", grouting modification technology can effectively control the deformation of tunnels by forming a reinforcement layer, and is an effective way to reinforce tunnel surrounding rock. However, in the grouting of loose and broken tunnels, organic grouting materials are expensive and cause serious pollution; while inorganic grouting materials represented by silicate cement have a long solidification time, which is difficult to solidify quickly during the grouting process of loose and broken coal mine tunnels, which easily causes slurry to flow out along the loose and broken cracks, and fails to ensure sufficient slurry to be injected into the tunnel surrounding rock, resulting in serious slurry leakage. When grouting and reinforcing loose and broken coal mine tunnels, the slurry intake is small, the leakage is serious, and the reinforcement effect is limited, which seriously affects the grouting effect and is the main restrictive factor for grouting and reinforcing the surrounding rock of loose and broken tunnels. Therefore, it is urgent to develop grouting materials suitable for loose and broken coal tunnels in coal mines to solve the problem of slurry leakage in loose and broken coal mine tunnels. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a grouting material based on in-situ polymerization modification of dopamine and a preparation method and application thereof.

[0004] In a first aspect, an embodiment of the present invention provides a grouting material based on in-situ polymerization modification of dopamine, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is (0.8-1.2):(0.8-1.2);

[0005] The component A comprises the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15-20 parts of dopamine active monomer, 1-2 parts of fluid loss reducer, and 1-3 parts of enhancer;

[0006] The B component includes the following components in parts by weight: 100 parts of gypsum, 2-5 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1-2 parts of toughening agent, and 1-3 parts of coagulant.

[0007] In some embodiments, in the A component, the fluid loss additive is a mixture of N-vinyl pyrrolidone copolymer, N-methyl-N-vinylacetamide copolymer and 2-acrylamide-2-methylpropanesulfonic acid copolymer;

[0008] Preferably, the mass ratio of the N-vinyl pyrrolidone copolymer, the N-methyl-N-vinylacetamide copolymer and the 2-acrylamide-2-methylpropanesulfonic acid copolymer is 2:(3-5):1, preferably 2:4:1.

[0009] In some embodiments, in the component A, the reinforcing agent is a mixture of nano-calcium carbonate, nano-magnesium carbonate and nano-barium carbonate;

[0010] Preferably, the mass ratio of the nano-calcium carbonate, the nano-magnesium carbonate and the nano-barium carbonate is 2:(0.5-1.5):2, preferably 2:1:2.

[0011] In some embodiments, in the B component, the polymerization catalyst is a mixture of antimony trioxide, antimony acetate and ethylene glycol antimony;

[0012] Preferably, the mass ratio of the antimony trioxide, the antimony acetate and the antimony glycolate is 1:4:(2-3), preferably 1:4:3.

[0013] In some embodiments, in the B component, the polymerization catalyst promoter is a mixture of barium sulfate, cesium sulfate and strontium sulfate;

[0014] Preferably, the mass ratio of the barium sulfate, the cesium sulfate and the strontium sulfate is 1:(5-8):1, preferably 1:6:1.

[0015] In some embodiments, in the B component, the toughening agent is a mixture of 1,7-octadiene and 1-butene block copolymer nanoparticles, 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles;

[0016] Preferably, the mass ratio of the 1,7-octadiene and 1-butene block copolymer nanoparticles to the 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles is 1:(2-4), preferably 1:3.

[0017] In some embodiments, in the B component, the coagulant is a mixture of indium oxide nanoparticles and nickel oxide nanoparticles;

[0018] Preferably, the mass ratio of the indium oxide nanoparticles to the nickel oxide nanoparticles is 1:1.

[0019] In a second aspect, the embodiment of the present invention further proposes a method for preparing a grouting material based on in-situ polymerization modification of dopamine as described in the first aspect, comprising the following steps:

[0020] S1, weighing fluoroaluminate cement clinker, sulphoaluminate cement clinker, dopamine active monomer, fluid loss additive and enhancer respectively according to their weight proportions, stirring and mixing, and obtaining component A;

[0021] S2, weighing gypsum, polymerization catalyst, polymerization catalyst accelerator, toughening agent and coagulant according to their weight parts respectively, stirring and mixing, and obtaining component B;

[0022] S3, adding water to the component A and the component B respectively, stirring and mixing, to obtain a component A slurry and a component B slurry, and the two slurries are mixed to obtain the grouting material based on dopamine in-situ polymerization modification.

[0023] In some embodiments, in step S1, the stirring and mixing temperature is 20-40° C., and the mixing time is 10-30 min;

[0024] And / or, in step S2, the stirring and mixing temperature is 20-40° C., and the mixing time is 10-30 min;

[0025] And / or, in step S3, the water-cement ratio of the component A slurry and the component B slurry are both 0.6-0.8.

[0026] In a third aspect, the embodiments of the present invention further propose the use of the grouting material based on in-situ polymerization modification of dopamine as described in the first aspect in loose and broken coal lanes in coal mines.

[0027] The advantages and beneficial effects of the embodiments of the present invention are as follows:

[0028] (1) The embodiment of the present invention optimizes the formula composition of the grouting material. By adding dopamine active monomer, fluid loss reducer, enhancer, polymerization catalyst, polymerization catalyst promoter, toughening agent and coagulant to the A and B components of the grouting material respectively, the hydration and hardening of the grouting material can be promoted, thereby improving the strength and toughness of the grouting stone body and improving the grouting reinforcement effect.

[0029] (2) When the grouting material of the embodiment of the present invention is used for on-site grouting, the dopamine active monomer in component A of the grouting material reacts with the polymerization catalyst and polymerization catalyst promoter in component B to undergo an in-situ polymerization reaction, which can rapidly solidify the grouting liquid and avoid leakage, thereby solving the serious leakage problem in loose and broken coal mine tunnels; and after the polymerization of the dopamine active monomer is completed, an amide bond structure is formed, which forms multiple hydrogen bonds with the hydroxyl and carboxyl groups on the surface of the coal body, thereby increasing the bonding strength between the grouting material and the coal body interface, thereby improving the grouting effect.

[0030] (3) In the grouting material of the embodiment of the present invention, polydopamine macromolecules are formed by in-situ polymerization, which have an amphiphilic structure and can form a molecular bridge between the interface of the organic coal body and the inorganic grouting body, which is beneficial to improve the bonding strength between the coal body and the grouting body interface and further improve the grouting effect.

[0031] (4) The grouting material in the embodiment of the present invention has a simple preparation process, is easy to operate, has low cost, and has a good grouting effect. It is particularly suitable for grouting reinforcement of loose and broken coal lanes in coal mines. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a process flow chart of a method for preparing a grouting material modified by in-situ polymerization of dopamine according to an embodiment of the present invention. DETAILED DESCRIPTION

[0033] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0034] Where values ​​are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values ​​falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.

[0035] Herein, the words "comprises" and "includes" and variations thereof mean that other elements or integers which are permitted but not specifically described may be included.

[0036] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0037] In a first aspect, an embodiment of the present invention provides a grouting material based on in-situ polymerization modification of dopamine, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is (0.8-1.2):(0.8-1.2);

[0038] The component A comprises the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15-20 parts of dopamine active monomer, 1-2 parts of fluid loss reducer, and 1-3 parts of enhancer;

[0039] The B component includes the following components in parts by weight: 100 parts of gypsum, 2-5 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1-2 parts of toughening agent, and 1-3 parts of coagulant.

[0040] In the embodiment of the present invention, dopamine active monomer is added to component A of the grouting material, and a polymerization catalyst and a polymerization catalyst promoter are added to component B of the grouting material. When grouting reinforcement is performed on site, slurries A and B are mixed, and a rapid in-situ polymerization reaction starts under the drive of the hydration heat of the cementitious material, so that the grouting liquid solidifies quickly to avoid leakage, thereby solving the serious leakage problem in loose and broken coal mine tunnels. After the polymerization of the dopamine active monomer is completed, an amide bond structure is formed, which forms multiple hydrogen bonds with the hydroxyl and carboxyl groups on the surface of the coal body, thereby increasing the bonding strength between the grouting material and the coal body interface, thereby improving the grouting control effect.

[0041] In the grouting material of the embodiment of the present invention, the polydopamine macromolecule formed by in-situ polymerization has an amphiphilic structure and can form a molecular bridge between the interface of the organic coal body and the inorganic grouting body, which is beneficial to improve the bonding strength between the coal body and the grouting body interface, thereby improving the grouting effect.

[0042] The embodiment of the present invention can promote the hydration and hardening of the grouting material, improve the strength and toughness of the grouting stone body, and improve the grouting reinforcement effect by adding dopamine active monomer, polymerization catalyst, polymerization catalyst accelerator, fluid loss reducer, reinforcing agent, toughening agent, and coagulant to the A and B components of the grouting material respectively.

[0043] In some embodiments, in the A component, the fluid loss additive is a mixture of N-vinyl pyrrolidone copolymer, N-methyl-N-vinylacetamide copolymer and 2-acrylamide-2-methylpropanesulfonic acid copolymer;

[0044] Preferably, the mass ratio of the N-vinyl pyrrolidone copolymer, the N-methyl-N-vinylacetamide copolymer and the 2-acrylamide-2-methylpropanesulfonic acid copolymer is 2:(3-5):1, non-limiting examples include: 2:3:1, 2:4:1, 2:5:1, etc.; preferably 2:4:1.

[0045] In some embodiments, in the component A, the reinforcing agent is a mixture of nano-calcium carbonate, nano-magnesium carbonate and nano-barium carbonate;

[0046] Preferably, the mass ratio of the nano-calcium carbonate, the nano-magnesium carbonate and the nano-barium carbonate is 2:(0.5-1.5):2, non-limiting examples include: 2:0.5:2, 2:1:2, 2:1.2:2, 2:1.5:2, etc.; preferably 2:1:2.

[0047] In some embodiments, in the B component, the polymerization catalyst is a mixture of antimony trioxide, antimony acetate and ethylene glycol antimony;

[0048] Preferably, the mass ratio of the antimony trioxide, the antimony acetate and the antimony glycolate is 1:4:(2-3), non-limiting examples include: 1:4:2, 1:4:2.5, 1:4:3, etc.; preferably 1:4:3.

[0049] In some embodiments, in the B component, the polymerization catalyst promoter is a mixture of barium sulfate, cesium sulfate and strontium sulfate;

[0050] Preferably, the mass ratio of the barium sulfate, the cesium sulfate and the strontium sulfate is 1:(5-8):1, non-limiting examples include: 1:5:1, 1:6:1, 1:7:1, 1:8:1, etc.; preferably 1:6:1.

[0051] In some embodiments, in the B component, the toughening agent is a mixture of 1,7-octadiene and 1-butene block copolymer nanoparticles, 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles;

[0052] Preferably, the mass ratio of the 1,7-octadiene and 1-butene block copolymer nanoparticles to the 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles is 1:(2-4), non-limiting examples include: 1:2, 1:3, 1:4, etc.; preferably 1:3.

[0053] In some embodiments, in the B component, the coagulant is a mixture of indium oxide nanoparticles and nickel oxide nanoparticles;

[0054] Preferably, the mass ratio of the indium oxide nanoparticles to the nickel oxide nanoparticles is 1:1.

[0055] In a second aspect, the embodiment of the present invention further proposes a method for preparing a grouting material based on in-situ polymerization modification of dopamine as described in the first aspect, comprising the following steps:

[0056] S1, weighing fluoroaluminate cement clinker, sulphoaluminate cement clinker, dopamine active monomer, fluid loss additive and enhancer respectively according to their weight proportions, stirring and mixing, and obtaining component A;

[0057] S2, weighing gypsum, polymerization catalyst, polymerization catalyst accelerator, toughening agent and coagulant according to their weight parts respectively, stirring and mixing, and obtaining component B;

[0058] S3, adding water to the component A and the component B respectively, stirring and mixing, to obtain a component A slurry and a component B slurry, and the two slurries are mixed to obtain the grouting material based on dopamine in-situ polymerization modification.

[0059] In some embodiments, in step S1, the stirring and mixing temperature is 20-40° C. (non-limiting examples include 20° C., 30° C., 35° C., 40° C., etc.), and the mixing time is 10-30 min (non-limiting examples include 10 min, 20 min, 25 min, 30 min, etc.);

[0060] And / or, in step S2, the stirring and mixing temperature is 20-40° C. (non-limiting examples: 20° C., 25° C., 30° C., 40° C., etc.), and the mixing time is 10-30 min (non-limiting examples: 10 min, 15 min, 20 min, 30 min, etc.);

[0061] And / or, in step S3, the water-cement ratio of the component A slurry and the component B slurry is 0.6-0.8, non-limiting examples are: 0.6, 0.7, 0.8, etc.

[0062] The method for preparing the grouting material based on the in-situ polymerization modification of dopamine in the embodiment of the present invention has simple process, easy operation, low raw material cost, is suitable for industrial large-scale production and application, and the grouting effect of the prepared grouting material is good.

[0063] In the third aspect, the embodiment of the present invention also proposes the application of the grouting material based on in-situ polymerization modification of dopamine as described in the first aspect in the loose and broken coal lanes of coal mines. When the grouting material based on in-situ polymerization modification of dopamine is used in the loose and broken coal lanes of coal mines, the grouting effect is good, and the problem of serious grout leakage in the loose and broken coal mine lanes can be solved.

[0064] The following are non-limiting examples and comparative examples of the present invention. It should be noted that the schemes of the comparative examples are not prior art and are only provided for comparison with the schemes of the embodiments and are not intended to limit the present invention. Unless otherwise specified, the various raw materials used in the embodiments and comparative examples are conventional commercial products or can be prepared by known methods.

[0065] Example 1

[0066] The grouting material based on dopamine in-situ polymerization modification of this embodiment includes component A and component B, and the mass ratio of component A to component B is 1:1;

[0067] Component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15 parts of dopamine active monomer, 1 part of fluid loss additive, and 1 part of enhancer;

[0068] Component B includes the following components in parts by weight: 100 parts of gypsum, 2 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 1 part of accelerator.

[0069] Among them, in component A, the fluid loss additive is a mixture of N-vinyl pyrrolidone copolymer, N-methyl-N-vinylacetamide copolymer and 2-acrylamide-2-methylpropanesulfonic acid copolymer; and the mass ratio of N-vinyl pyrrolidone copolymer, N-methyl-N-vinylacetamide copolymer and 2-acrylamide-2-methylpropanesulfonic acid copolymer is 2:4:1;

[0070] The reinforcing agent is a mixture of nano calcium carbonate, nano magnesium carbonate and nano barium carbonate; and the mass ratio of the nano calcium carbonate, nano magnesium carbonate and nano barium carbonate is 2:1:2.

[0071] In component B, the polymerization catalyst is a mixture of antimony trioxide, antimony acetate and ethylene glycol antimony; and the mass ratio of antimony trioxide, antimony acetate and ethylene glycol antimony is 1:4:3;

[0072] The polymerization catalyst promoter is a mixture of barium sulfate, cesium sulfate and strontium sulfate; and the mass ratio of barium sulfate, cesium sulfate and strontium sulfate is 1:6:1;

[0073] The toughening agent is a mixture of 1,7-octadiene and 1-butene block copolymer nanoparticles and 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles; and the mass ratio of 1,7-octadiene and 1-butene block copolymer nanoparticles to 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles is 1:3;

[0074] The coagulant is a mixture of indium oxide nanoparticles and nickel oxide nanoparticles; and the mass ratio of the indium oxide nanoparticles to the nickel oxide nanoparticles is 1:1.

[0075] The preparation method of the grouting material based on dopamine in-situ polymerization modification of this embodiment comprises the following steps:

[0076] S1, weigh 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15 parts of dopamine active monomer, 1 part of fluid loss additive and 1 part of enhancer respectively according to their mass parts, add them into a dry powder mixer, stir and mix at 20°C for 20 minutes to obtain a uniform powder, which is component A;

[0077] S2, weigh 100 parts of gypsum, 2 parts of polymerization catalyst, 1 part of polymerization catalyst promoter, 1 part of toughening agent and 1 part of coagulant according to their mass parts, add them into a dry powder mixer, stir and mix at 20°C for 20 minutes to obtain a uniform powder, which is component B;

[0078] S3, adding water to component A and component B respectively and stirring, controlling the water-cement ratio to be 0.6, obtaining component A slurry and component B slurry respectively, and mixing the two slurries to obtain a grouting material based on dopamine in-situ polymerization modification.

[0079] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 44s, and the final setting time is 321s; and the compressive strength of the grouting material after 2h is 21MPa, and the flexural strength is 5.9MPa; the compressive strength of the grouting material after 28h is 42MPa.

[0080] Example 2

[0081] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 16 parts of dopamine active monomer, 2 parts of fluid loss additive, and 2 parts of enhancer;

[0082] Component B includes the following components in parts by weight: 100 parts of gypsum, 3 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 2 parts of coagulant.

[0083] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 46s, and the final setting time is 334s; the compressive strength of the grouting material after 2h is 24MPa, and the flexural strength is 5.7MPa; the compressive strength of the grouting material after 28h is 41MPa.

[0084] Example 3

[0085] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 17 parts of dopamine active monomer, 2 parts of fluid loss additive, and 3 parts of enhancer;

[0086] Component B includes the following components in parts by weight: 100 parts of gypsum, 4 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 3 parts of accelerator.

[0087] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 49s, and the final setting time is 351s; the compressive strength of the grouting material after 2h is 20MPa, and the flexural strength is 5.9MPa; the compressive strength of the grouting material after 28h is 45MPa.

[0088] Example 4

[0089] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 18 parts of dopamine active monomer, 1 part of fluid loss additive, and 2 parts of enhancer;

[0090] Component B includes the following components in parts by weight: 100 parts of gypsum, 5 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 2 parts of accelerator.

[0091] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 52s, and the final setting time is 359s; the compressive strength of the grouting material after 2h is 19MPa, and the flexural strength is 5.4MPa; the compressive strength of the grouting material after 28h is 49MPa.

[0092] Example 5

[0093] This embodiment is basically the same as Embodiment 1, except that:

[0094] Component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 19 parts of dopamine active monomer, 1 part of fluid loss additive, and 3 parts of enhancer;

[0095] Component B includes the following components in parts by weight: 100 parts of gypsum, 4 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 3 parts of accelerator.

[0096] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 57s, and the final setting time is 367s; the compressive strength of the grouting material after 2h is 21MPa, and the flexural strength is 6.3MPa; the compressive strength of the grouting material after 28h is 42MPa.

[0097] Example 6

[0098] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 20 parts of dopamine active monomer, 2 parts of fluid loss additive, and 1 part of enhancer;

[0099] Component B includes the following components in parts by weight: 100 parts of gypsum, 2 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 1 part of accelerator.

[0100] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 45s, and the final setting time is 325s; the compressive strength of the grouting material after 2h is 23MPa, and the flexural strength is 5.6MPa; the compressive strength of the grouting material after 28h is 43MPa.

[0101] Example 7

[0102] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15 parts of dopamine active monomer, 2 parts of fluid loss additive, and 3 parts of enhancer;

[0103] Component B includes the following components in parts by weight: 100 parts of gypsum, 5 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 3 parts of accelerator.

[0104] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 47s, and the final setting time is 341s; the compressive strength of the grouting material after 2h is 22MPa, and the flexural strength is 5.5MPa; the compressive strength of the grouting material after 28h is 41MPa.

[0105] Example 8

[0106] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 16 parts of dopamine active monomer, 1 part of fluid loss additive, and 2 parts of enhancer;

[0107] Component B includes the following components in parts by weight: 100 parts of gypsum, 4 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 2 parts of accelerator.

[0108] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 50s, and the final setting time is 354s; the compressive strength of the grouting material after 2h is 20MPa, and the flexural strength is 6.1MPa; the compressive strength of the grouting material after 28h is 44MPa.

[0109] Example 9

[0110] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 17 parts of dopamine active monomer, 1 part of fluid loss additive, and 1 part of enhancer;

[0111] Component B includes the following components in parts by weight: 100 parts of gypsum, 3 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 1 part of accelerator.

[0112] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 55s, and the final setting time is 365s; the compressive strength of the grouting material after 2h is 18MPa, and the flexural strength is 5.4MPa; the compressive strength of the grouting material after 28h is 47MPa.

[0113] Example 10

[0114] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 18 parts of dopamine active monomer, 2 parts of fluid loss additive, and 1 part of enhancer;

[0115] Component B includes the following components in parts by weight: 100 parts of gypsum, 2 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 1 part of accelerator.

[0116] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 48s, and the final setting time is 347s; the compressive strength of the grouting material after 2h is 21MPa, and the flexural strength is 5.8MPa; the compressive strength of the grouting material after 28h is 43MPa.

[0117] Embodiment 11

[0118] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 19 parts of dopamine active monomer, 2 parts of fluid loss additive, and 2 parts of enhancer;

[0119] Component B includes the following components in parts by weight: 100 parts of gypsum, 4 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 2 parts of toughening agent, and 2 parts of coagulant.

[0120] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 51s, and the final setting time is 357s; the compressive strength of the grouting material after 2h is 19MPa, and the flexural strength is 6.2MPa; the compressive strength of the grouting material after 28h is 42MPa.

[0121] Example 12

[0122] This embodiment is basically the same as embodiment 1, except that: component A includes the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 20 parts of dopamine active monomer, 1 part of fluid loss additive, and 2 parts of enhancer;

[0123] Component B includes the following components in parts by weight: 100 parts of gypsum, 5 parts of polymerization catalyst, 1 part of polymerization catalyst accelerator, 1 part of toughening agent, and 2 parts of accelerator.

[0124] After testing, the initial setting time of the grouting material based on dopamine in-situ polymerization modification prepared in this embodiment is 53s, and the final setting time is 361s; the compressive strength of the grouting material after 2h is 25MPa, and the flexural strength is 5.7MPa; the compressive strength of the grouting material after 28h is 45MPa.

[0125] Comparative Example 1

[0126] This comparative example is substantially the same as Example 1, except that component A does not contain dopamine active monomer.

[0127] After testing, the initial setting time of the grouting material prepared in this comparative example is 280s, and the final setting time is 30min; the compressive strength of the grouting material after 2h is 6MPa, and the flexural strength is 1.9MPa; the compressive strength of the grouting material after 28h is 18MPa.

[0128] Comparative Example 2

[0129] This comparative example is substantially the same as Example 1, except that component B does not contain a polymerization catalyst.

[0130] After testing, the initial setting time of the grouting material prepared in this comparative example is 230s, and the final setting time is 26min; the compressive strength of the grouting material after 2h is 8MPa, and the flexural strength is 2.5MPa; the compressive strength of the grouting material after 28h is 22MPa.

[0131] Comparative Example 3

[0132] This comparative example is substantially the same as Example 1, except that component B does not contain a polymerization catalyst promoter.

[0133] After testing, the initial setting time of the grouting material prepared in this comparative example is 200s, and the final setting time is 22min; the compressive strength of the grouting material after 2h is 9MPa, and the flexural strength is 2.8MPa; the compressive strength of the grouting material after 28h is 24MPa.

[0134] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0135] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A grouting material based on in-situ polymerization modification of dopamine, characterized in that: It comprises a component A and a component B, wherein the mass ratio of the component A to the component B is (0.8-1.2):(0.8-1.2); The component A comprises the following components in parts by weight: 50 parts of fluoroaluminate cement clinker, 50 parts of sulphoaluminate cement clinker, 15-20 parts of dopamine active monomer, 1-2 parts of fluid loss reducer, and 1-3 parts of enhancer; The B component includes the following components in parts by mass: 100 parts of gypsum, 2-5 parts of polymerization catalyst, 1 part of polymerization catalyst promoter, 1-2 parts of toughening agent, and 1-3 parts of accelerator; wherein the polymerization catalyst is a mixture of antimony trioxide, antimony acetate and ethylene glycol antimony, and the mass ratio of the antimony trioxide, the antimony acetate and the ethylene glycol antimony is 1:4:(2-3); the polymerization catalyst promoter is a mixture of barium sulfate, cesium sulfate and strontium sulfate, and the mass ratio of the barium sulfate, the cesium sulfate and the strontium sulfate is 1:(5-8):

1.

2. The grouting material based on in-situ polymerization modification of dopamine according to claim 1, characterized in that: In the component A, the fluid loss additive is a mixture of N-vinyl pyrrolidone copolymer, N-methyl-N-vinylacetamide copolymer and 2-acrylamide-2-methylpropanesulfonic acid copolymer; the mass ratio of the N-vinyl pyrrolidone copolymer, the N-methyl-N-vinylacetamide copolymer and the 2-acrylamide-2-methylpropanesulfonic acid copolymer is 2:(3-5):

1.

3. The grouting material based on dopamine in-situ polymerization modification according to claim 1, characterized in that: In the component A, the reinforcing agent is a mixture of nano-calcium carbonate, nano-magnesium carbonate and nano-barium carbonate; the mass ratio of the nano-calcium carbonate, the nano-magnesium carbonate and the nano-barium carbonate is 2:(0.5-1.5):

2.

4. The grouting material based on in-situ polymerization modification of dopamine according to claim 1, characterized in that: In the B component, the toughening agent is a mixture of 1,7-octadiene and 1-butene block copolymer nanoparticles and 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles; the mass ratio of the 1,7-octadiene and 1-butene block copolymer nanoparticles to the 7-methyl-1,6-octadiene and ethylene, propylene copolymer nanoparticles is 1:(2-4).

5. The grouting material based on dopamine in-situ polymerization modification according to claim 1, characterized in that: In the B component, the coagulant is a mixture of indium oxide nanoparticles and nickel oxide nanoparticles; the mass ratio of the indium oxide nanoparticles to the nickel oxide nanoparticles is 1:

1.

6. A method for preparing a grouting material based on in-situ polymerization modification of dopamine as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1, weighing fluoroaluminate cement clinker, sulphoaluminate cement clinker, dopamine active monomer, fluid loss additive and enhancer respectively according to their weight proportions, stirring and mixing, and obtaining component A; S2, weighing gypsum, polymerization catalyst, polymerization catalyst accelerator, toughening agent and coagulant according to their weight parts respectively, stirring and mixing, and obtaining component B; S3, adding water to the component A and the component B respectively, stirring and mixing, to obtain a component A slurry and a component B slurry, and the two slurries are mixed to obtain the grouting material based on dopamine in-situ polymerization modification.

7. The method for preparing a grouting material based on in-situ polymerization modification of dopamine according to claim 6, characterized in that: In step S1, the stirring and mixing temperature is 20-40°C and the mixing time is 10-30min; And / or, in step S2, the stirring and mixing temperature is 20-40° C., and the mixing time is 10-30 min; And / or, in step S3, the water-cement ratio of the component A slurry and the component B slurry are both 0.6-0.

8.

8. Use of a grouting material based on in-situ polymerization modification of dopamine as described in any one of claims 1 to 5 in loose and broken coal lanes in coal mines.

Citation Information

Patent Citations

  • Mining low-temperature ultrahigh crystal water quick-setting filling support material and preparation method thereof

    CN115073117A

  • Fast-hardening cement concrete composition with high strength and repairing method of road pavement using the same

    KR102364286B1